Chronic graft-versus-host disease: clinical presentation of multiple lesions of lichenoid and atrophic pattern - Luiza Vasconcelos; Erica Cristina Vieira; Eliana Maria Minicucci; Ana Gabriela Salvio; Mair Pedro de Souza; Mariangela Esther Alencar Marques; Silvio Alencar Marques (Sociedade Brasileira de Dermatologia, 2013)
Graft-versus-host disease is observed mainly in recipients of hematopoietic cell transplantation and is expressed by cutaneous or systemic signals and symptoms. Graft-versus-host disease is clinically classified as acute or chronic. Chronic Graft-versus-host disease occurs in up to 70% of hematopoietic cell transplanted patients and its clinical manifestations have important impact on morbidity and quality of life. The authors report an expressive cutaneous, oral and adnexal involvement in a patient with chronic Graft-versus-host disease with multiple lesions of lichenoid and atrophic pattern.